2013
DOI: 10.1007/s00429-012-0501-7
|View full text |Cite
|
Sign up to set email alerts
|

Musculotopic organization of the motor neurons supplying the mouse hindlimb muscles: a quantitative study using Fluoro-Gold retrograde tracing

Abstract: We have mapped the motor neurons (MNs) supplying the major hindlimb muscles of transgenic (C57/BL6J-ChAT-EGFP) and wild-type (C57/BL6J) mice. The fluorescent retrograde tracer Fluoro-Gold was injected into 19 hindlimb muscles. Consecutive transverse spinal cord sections were harvested, the MNs counted, and the MN columns reconstructed in 3D. Three longitudinal MN columns were identified. The dorsolateral column extends from L4 to L6 and consists of MNs innervating the crural muscles and the foot. The ventrolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 53 publications
(52 reference statements)
3
25
0
Order By: Relevance
“…These muscles are involved in maintaining posture and locomotion 15 and are involved in the righting reflex which is impaired in SMA mouse models 13 . The IL/QL MNs reside within the L1 to L3 spinal segments 16 . Tracing experiments from muscle together with ventral root L2 fill, indicated that the largest portion of IL/QL MNs lie laterally within the L2 spinal segment (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These muscles are involved in maintaining posture and locomotion 15 and are involved in the righting reflex which is impaired in SMA mouse models 13 . The IL/QL MNs reside within the L1 to L3 spinal segments 16 . Tracing experiments from muscle together with ventral root L2 fill, indicated that the largest portion of IL/QL MNs lie laterally within the L2 spinal segment (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The approach we present takes advantage of the preserved organization of lumbosacral motoneuron pools among species, including in cat [13, 14], rat [20], mouse [21], monkey and human (current study). The iliospoas motoneuronal cell group was chosen as the rostral landmark in both cat [13] and monkey (this study) as this cell group represents the most rostral cluster of hindlimb motoneurons in the lumbar enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…The iliospoas motoneuronal cell group was chosen as the rostral landmark in both cat [13] and monkey (this study) as this cell group represents the most rostral cluster of hindlimb motoneurons in the lumbar enlargement. Though studies involving the position of iliopsoas motoneurons in other species are sparse, psoas motoneurons also consistently form a compact cluster in the ventrolateral corner of the ventral horn of the rostral part of the enlargement in rat and mice [20, 21]. Species differences relate largely to the assigned segmental level, further supporting the advantage of using a relative scale to compare levels rather than segmental levels.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, their work has established that motor neurons in the ventral horn of the spinal cord that innervate skeletal muscles are arranged into longitudinal columns. More recently, retrograde tracers, either applied to the peripheral nerve stump or injected intramuscularly, have been instrumental in defining the connectivity between individual skeletal muscles and the innervating motor neuron columns in various mammalian species (Kristensson and Olsson, 1971a,b; McHanwell and Biscoe, 1981; Jenny and Inukai, 1983; Nicolopoulos-Stournaras and Iles, 1983; Brichta et al, 1987; Callister et al, 1987; Hörner and Kümmel, 1993; Novikova et al, 1997; Vanderhorst and Holstege, 1997; McKenna et al, 2000; Choi et al, 2002; Tosolini and Morris, 2012; Bácskai et al, 2013a,b). Together, these studies further characterize the organization of motor neuron columns throughout the spinal cord.…”
Section: Introductionmentioning
confidence: 99%